Freeze gelation 3D printing of rGO-CuCo2S4 nanocomposite for high-performance supercapacitor electrodes. (1st October 2021) - Tung, Doan Thanh; Tam, Le Thi Thanh; Dung, Hoang Tran; Dung, Ngo Thanh; Hong, Phan Ngoc; Nguyet, Ha Minh; Van-Quynh, Nguyen; Van Chuc, Nguyen; Trung, Vu Quoc; Lu, Le Trong; Minh, Phan Ngoc
Highlight: A homogeneous hybrid nano ink based on rGO-CuCo2 S4 nanocomposites. A judicious combination of the freeze gelation method and 3D printing technique for the fabrication of high porosity material. The supercapacitor electrodes with high specific capacitance and excellent capacitance retention. Abstract: Reduced graphene oxide (rGO)-CuCo2 S4 nanocomposites are synthesized by a facile hydrothermal method. Thiourea has been used as a sulfur source for synthesizing CuCo2 S4 nanoparticles. The synthesized materials are then dispersed in phenol with the addition of Polyvinylpyrrolidone (PVP), which acts as a binder to form the homogeneous rGO-CuCo2 S4 slurry. This as-prepared slurry is then deposited on the graphite paper using 3D printing technique combined with the freeze gelation method to form a rGO - CuCo2 S4 electrode. X-ray diffractometry (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS) and electrochemical techniques have been used to characterize rGO-CuCo2 S4 nanocomposite. The nanocomposite has a microporous structure with CuCo2 S4 nanoparticles decorated on the rGO sheet surface. Electrochemical studies revealed that the rGO-CuCo2 S4 nanocomposite electrode has a high specific capacitance of ca. 1123 F/g at 5 mV/s and excellent capacitance retention. A 91% capacitance remained approximately after 20000 successive cycles at a high current density of 125 A/g are remarkable and it has not been widely reported for a supercapacitor electrode. Graphical abstract: Image, graphical abstract